Chemoenzymatic, biomimetic total synthesis of (−)-rugulosin B, C and rugulin analogues and their biosynthetic implications. Issue 22 (24th February 2020) - Mondal, Amit; Singh, Shailesh Kumar; Manna, Tanaya; Husain, Syed Masood
Abstract : Flavoskyrins, (−)-rugulosin B, C and rugulin analogues are synthesized chemoenzymatically from anthraquinones in two, three and four steps, respectively. Abstract : Herein, we report the chemoenzymatic synthesis of a heterodimeric (−)-rugulosin B, homodimeric (−)-rugulosin C, and several rugulin analogues in three to four steps starting from anthraquinones. This work supports dimerization between variously substituted putative monomeric intermediates during the biosynthesis of naturally occurring (+)-rugulosin B and C.